2019
DOI: 10.1186/s13039-019-0461-1
|View full text |Cite
|
Sign up to set email alerts
|

A prenatal diagnosis and genetics study of five pedigrees in the Chinese population with Xp22.31 microduplication

Abstract: BackgroundCopy number variations (CNVs) can contribute to human phenotype, phenotypic diversity and disease susceptibility, while others may benign. In the current study, an attempt to investigate the pathogenicity of CNVs in chromosome Xp22.31 was explored.MethodsG-banding and SNP-array techniques were used to analyze chromosome karyotypes and CNVs in fetuses. Parents associate with five different pedigrees possessing high risk factors in pregnancy were considered with such parameters as advanced age, high ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Hence, duplications could potentially have dissociable effects on depressive and manic traits, acting to reduce the former whilst eliciting the latter. In terms of neuroanatomy, duplication carriers also exhibited evidence for enlarged left lateral ventricle volume relative to controls; this finding aligns with a previous observation of a widened left lateral ventricle in a fetus possessing an Xp22.31 1.6 Mb microduplication ( 21 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, duplications could potentially have dissociable effects on depressive and manic traits, acting to reduce the former whilst eliciting the latter. In terms of neuroanatomy, duplication carriers also exhibited evidence for enlarged left lateral ventricle volume relative to controls; this finding aligns with a previous observation of a widened left lateral ventricle in a fetus possessing an Xp22.31 1.6 Mb microduplication ( 21 ).…”
Section: Discussionsupporting
confidence: 89%
“…Case series/studies documenting predominantly young, clinically-ascertained, individuals with Xp22.31 duplications report a number of neurological features including intellectual disability/cognitive impairment (40%), autism or autistic behaviours (10–20%), global developmental delay (10%), delayed speech and language (10%) and seizures (10%), as well as other less common clinical manifestations including microcephaly (5–10%), muscular hypotonia (5–10%) and clinodactyly or shortness of the fifth finger (5%) ( 10–20 ), and ( Supplementary Material, Table 1 ). Whether the Xp22.31 duplication is pathogenic (particularly with regard to its role in brain function and head/facial dysmorphism), or whether it is benign but tends to occur in combination with other pathogenic mechanisms, has been a matter for debate ( 21–23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that some individuals with duplication of this region had varied degrees of neurological impairment, including growth retardation, intellectual disability, autistic spectrum disorders, hypotonia, seizures, psychomotor retardation, and mild special face ( Faletra et al, 2012 ; Pavone et al, 2019 ; Polo-Antunez & Arroyo-Carrera, 2017 ). Some studies showed that duplication of Xp22.31 is a risk factor for abnormal phenotypes or benign variants ( Liu et al, 2011 ; Zhuang et al, 2019 ). In this study, we found that five babies with Xp22.31 duplication did not present with phenotypes during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2–3 ml peripheral blood were collected from the patient and the parents for karyotype analysis. The peripheral blood lymphocytes were harvested using a SinochromeChromprepII automatic chromosome harvesting system according to the standard protocol (Shanghai Lechen Biotechnology Co., Ltd.), which has been described previously in our study [ 13 ]. After staining with Giemsa stain, twenty karyotypes were counted and analyzed five karyotypes.…”
Section: Methodsmentioning
confidence: 99%